Analysis of the Ccr4-Not deadenylase complex: a biochemical and computational approach - Balacco, Dario Leonardo (2017)
In eukaryotic cells, the degradation of the mRNA poly(A) tail (deadenylation) is a crucial step in the regulation of gene expression. The Ccr4-Not complex is the major deadenylase enzyme involved in the mRNA deadenylation. The complex is composed by two subunits with ribonuclease activity (Caf1 and Ccr4) and at least six non-catalytic subunits. In vertebrate cells, the duplication of the catalytic subunits Caf1 (encoded by CNOT7 and CNOT8) and Ccr4 (encoded by CNOT6 and CNOT6L) lead to the heterogeneity of the complex. The non-catalytic subunits are organised in modules, each with a specific function, allowing the recruitment of the complex on specific mRNAs. Regulatory proteins interact with the deadenylase complex tethering it on specific mRNAs and activating mRNA degradation pathways and down regulating protein expression. This study discovered and explored the interactome of the catalytic subunits Caf1 and Ccr4 and detected new interacting partners that may recruit the deadenylase complex on specific mRNAs. Nowadays, genotyping patients using whole genome and next generation sequencing technologies, allows a wider but more accurate sight of the genomic contest of a specific disease. The alteration of the function or the structure of the Ccr4-Not complex in cancer was assessed investigating the structure and function of the variants of the components of the NOT-module (CNOT1, CNOT2 and CNOT3) and the nuclease sub complex (CNOT7, CNOT6L, CNOT1, and the regulatory protein BTG1) found in various types of cancers. Finally, phylogenetic analysis of 15 mammalian species identified different evolutionary rates acting on the paralogous deadenylase subunits.